2016
DOI: 10.3390/su8121228
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Gilthead Seabream (Sparus aurata) Production in Offshore Fish Farms

Abstract: Abstract:Life cycle assessment is used in this study to evaluate the potential environmental impacts of producing gilthead seabream in an offshore sea farm exposed to storms in the Spanish Mediterranean Sea. The farming methods used can be considered as "basic" since no centralized or automatic food distribution system exists and there is no control system. This study aims to identify the main hotspots under these conditions and to propose and compare viable alternatives to them. Contribution analysis found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 54 publications
6
45
1
Order By: Relevance
“…The environmental effects of infrastructure were found to be at 52% for abiotic depletion (ABD), 49% for global warming (GW), 3% for ozone layer depletion (OLD), 30% for human toxicity (HT), 2% Based on the LCA study conducted, it was found that effects from ingredients in fish feed contributed an average of 55% to all the identified environmental impact categories. These findings are in line with other studies [19,27,32] which stated that feeding has the highest impact on the environment. Fish farming infrastructure contributed an average of 33%, while the effects from the operation of fish farming activities contributed an average of 12% to all the identified environmental impact categories, as shown in Figure 4.…”
Section: Infrastructuresupporting
confidence: 93%
See 3 more Smart Citations
“…The environmental effects of infrastructure were found to be at 52% for abiotic depletion (ABD), 49% for global warming (GW), 3% for ozone layer depletion (OLD), 30% for human toxicity (HT), 2% Based on the LCA study conducted, it was found that effects from ingredients in fish feed contributed an average of 55% to all the identified environmental impact categories. These findings are in line with other studies [19,27,32] which stated that feeding has the highest impact on the environment. Fish farming infrastructure contributed an average of 33%, while the effects from the operation of fish farming activities contributed an average of 12% to all the identified environmental impact categories, as shown in Figure 4.…”
Section: Infrastructuresupporting
confidence: 93%
“…Fish meal and soybean meal were the feed materials which contributed most to ABD and GW. Consistent with previous research [19], this fact is closely linked to the demand of great amounts of these materials according to the current fish feed formulation. Moreover, if global warming is of particular interest, additional hotspots would also include transport and the emissions to the air from boilers in feed processing [38].…”
Section: Analysis On Feeding Ingredientssupporting
confidence: 88%
See 2 more Smart Citations
“…), offshore aquaculture systems (García García et al . ) or shellfish production farms (Lourguioui et al . ).…”
Section: Distribution Of Environmental Impacts Within Aquaculture Sysmentioning
confidence: 99%